Supply Stability and Battery Protection in Rooftop Solar Pv System: A Hybrid Energy Approach - Sari, Desti Erwita; Rusdianasari; Taqwa, Ahamad (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
This study looks at how a hybrid rooftop solar power system works when connected to the national electricity grid, and how well it keeps the power supply steady for constant loads. The research has three main goals: setting up the hybrid energy system properly, protecting the batteries from damage, and using IoT technology to keep track of and control the system. Data was gathered over two weeks using a real-time monitoring tool called Adafruit IO. They checked several things like current, voltage, power flow, and how well the batteries were performing, including their charge level and how much they were being used. The results show the hybrid solar and grid setup works well. It uses solar power whenever it’s available and switches automatically to the grid when there’s not enough sunlight. The batteries stayed fully charged at 100%, which means they weren’t being used much and weren’t getting worn out quickly, helping them last longer and work better. Also, using IoT made it possible to monitor the system from a distance, collect data in real time, and make decisions automatically. This helped track how much energy was being made and used, spot any problems early, and control the power sources smartly. The research shows that this hybrid solar system, with IoT monitoring is a good way to keep the power steady for constant needs while keeping the batteries in good shape.